Candida albicans Chitin Increases Arginase-1 Activity in Human Macrophages, with an Impact on Macrophage Antimicrobial Functions - Jeanette Wagener; Donna M. MacCallum; Gordon D. Brown; Neil A. R. Gow (mBio, 2017)
ABSTRACT The opportunistic human fungal pathogen Candida albicans can cause a variety of diseases, ranging from superficial mucosal infections to life-threatening systemic infections. Phagocytic cells of the innate immune response, such as neutrophils and macrophages, are important first-line responders to an infection and generate reactive oxygen and nitrogen species as part of their protective antimicrobial response. During an infection, host cells generate nitric oxide through the enzyme inducible nitric oxide synthase (iNOS) to kill the invading pathogen. Inside the phagocyte, iNOS competes with the enzyme arginase-1 for a common substrate, the amino acid l-arginine. Several pathogenic species, including bacteria and parasitic protozoans, actively modulate the production of nitric oxide by inducing their own arginases or the host’s arginase activity to prevent the conversion of l-arginine to nitric oxide. We report here that C. albicans blocks nitric oxide production in human-monocyte-derived macrophages by induction of host arginase activity. We further determined that purified chitin (a fungal cell wall polysaccharide) and increased chitin exposure at the fungal cell wall surface induces this host arginase activity. Blocking the C. albicans-induced arginase activity with the arginase-specific substrate inhibitor Nω-hydroxy-nor-arginine (nor-NOHA) or the chitinase inhibitor bisdionin F restored nitric oxide production and increased the efficiency of fungal killing. Moreover, we determined that C. albicans influences macrophage polarization from a classically activated phenotype toward an alternatively activated phenotype, thereby reducing antimicrobial functions and mediating fungal survival. Therefore, C. albicans modulates l-arginine metabolism in macrophages during an infection, potentiating its own survival. IMPORTANCE The availability and metabolism of amino acids are increasingly recognized as crucial regulators of immune functions. In acute infections, the conversion of the “conditionally essential” amino acid l-arginine by the inducible nitric oxide synthase to nitric oxide is a resistance factor that is produced by the host to fight pathogens. Manipulation of these host defense mechanisms by the pathogen can be key to successful host invasion. We show here that the human opportunistic fungal pathogen Candida albicans influences l-arginine availability for nitric oxide production by induction of the substrate-competing host enzyme arginase-1. This led to a reduced production of nitric oxide and, moreover, reduced eradication of the fungus by human macrophages. We demonstrate that blocking of host arginase-1 activity restored nitric oxide production and increased the killing potential of macrophages. These results highlight the therapeutic potential of l-arginine metabolism in fungal diseases.